UPAYA MENINGKATKAN RASA PERCAYA DIRI ANAK MELALUI METODE BERCERITA PADA KELOMPOK A DI TK PGRI MELUR - Yuli Susanti; Ibnu Hurri; Alfian Ashshidiqi Poppyariyana (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to improve the self-confidence of early childhood through storytelling methods in Group A of PGRI Melur Kindergarten. Self-confidence is an important aspect in children's development, which plays a role in shaping their social, communication, and independence skills. Based on initial observations, it was found that most children in this group had low levels of self-confidence, characterized by reluctance to speak in public, a soft voice when speaking, giving up easily when facing tasks, and dependence on teachers or parents in completing tasks. The research method used was Classroom Action Research (CAR) with the Kemmis and McTaggart model consisting of two cycles. Each cycle includes the planning, implementation, observation, and reflection stages. The subjects of the study were 18 children in Group A of PGRI Melur Kindergarten. Data were collected through observation, documentation, and interviews, which were then analyzed using qualitative descriptive methods. The results showed that the storytelling method significantly increased children's self-confidence. Children were more active in speaking, more confident in presenting stories in front of their friends, and showed enthusiasm in participating in learning activities. In addition, this study identified several obstacles in the application of the storytelling method, such as the lack of focus of children in listening to stories and differences in the level of language development between them. Therefore, the storytelling method has proven to be an effective strategy in increasing the self-confidence of early childhood. It is hoped that the results of this study can be a reference for educators and parents in developing more innovative and enjoyable learning methods for early childhood.